+0  
 
+1
271
2
avatar

What is 6(x-6)-5(x-7)=x+6?

Guest Mar 20, 2017
 #1
avatar+12560 
+1

First step...use distributive propety to expand to:

6x - 36 - 5x + 35 = x+6     gather like terms

x - 1 = x + 6        Uh - Oh      there is no solution to this !

ElectricPavlov  Mar 20, 2017
 #2
avatar+7002 
0

6(x-6)-5(x-7)=x+6

6x-36-5x+35 = x+6

x - 1 = x + 6 WHAT!????

MaxWong  Mar 23, 2017

9 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.